The Transformation of the Tahlilan Tradition from 2010 to 2025 in Buluh Cina Village - Dumel Awiyah Br Harahap; Nabila Yasmin (Medan Resource Center, 2026)
Tahlilan is a tradition deeply rooted in the culture of Indonesian Muslim society and is often regarded as an obligation to commemorate the deceased. For some people, tahlilan is not merely a religious activity but also reflects social dynamics in community interactions. Apart from its religious values, the tahlilan tradition also has social and economic impacts, particularly for families with financial limitations. This study employs a qualitative field research approach conducted in Desa Buluh Cina to examine tahlilan as a socio-religious practice and to explore how social pressure and economic burden shape its implementation within the community. The findings reveal that tahlilan in Desa Buluh Cina functions not only as a medium of collective remembrance but also as a site of social expectation, where participation is often driven by communal pressure rather than purely individual piety. Families with limited economic capacity experience a disproportionate burden, leading to a shift in the meaning of sincerity in worship from voluntary devotion to socially conditioned obligation. At the same time, adaptive practices emerge to negotiate between religious values and economic realities. These findings demonstrate that the transformation of tahlilan reflects broader socio-religious changes, where cultural continuity persists amid tensions between faith, social norms, and economic constraints.